EKSTERNALITAS MODEL ECO-SETTLEMENTS DI DAERAH ALIRAN SUNGAI (DAS) HULU CIMANUK (STUDI KASUS KAMPUNG MUARA, DESA SUKAWARGI, KECAMATAN CISURUPAN,KABUPATEN GARUT, JAWA BARAT) (Jurnal Social Economic of Agriculture, 2012)
Kampung Muara which is the upstream of Cimanuk watershed is oneof the areas experiencing environmental degradation caused by land use.In response to these problems, the Research Institute for HumanSettlements devised a model of eco-settlements as an upstream ofwatershed development. This research aims to determine the externalitiesrised from the implementation of eco-settlements model. The techniqueused for this research is case study, while design used is a descriptivemethod that is supported by primary and secondary data. The result of thisresearch shows that, the implementation of eco-settlements model canprovide external economy and lead to external diseconomy. Externaleconomy generated from tangible benefit and intangible benefit. Tangilblebenefits received by the community improvement of water quality andadditional income for the community. Intangible benefits gained from theimplementation of eco-settlements model is the presence of erosioncontrol, reduce risk of flooding, the formation of informal institutionPokjamas Hikmatul Jamaah, and knowledge improvement of the trainingprocess, particularly in the operation of the technology. Externaldiseconomy of the implementation eco-settlements model is the emergenceof dependence on government support.Keyword: External Economy and Extenal Diseconomy, Eco-settlements,Watershed.